A Simple and Effective Quantification of Water-Soluble Rhodium in Soil Samples by Magnetic-Colloidal-Gel-Assisted Dispersive Solid Phase Extraction - Cesur, Buket; Atsever, Nihan; Zaman, Buse Tugba; Bakirdere, Sezgin (WILEY-V C H VERLAG GMBH, 2023)
In this study, a simple, sensitive and environmentally friendly method was developed for the determination of water-soluble rhodium in soil samples. For this purpose, rhodium was preconcentrated/separated by a dispersive solid phase extraction method (dSPE) and determined by an atomic absorption spectrophotometer with flame atomizer, equipped with a slotted quartz tube (SQT-FAAS). In the dSPE method, a magnetic colloidal gel (magnetic nanofluid) was produced by mixing Fe3O4 based magnetic nanoparticles (MNP), and deep eutectic solvent (DES) obtained from the mixture of choline chloride and phenol (1 : 3). The optimized system showed good linearity in the concentration range of 17-447 mu g/kg. While recording a detection limit (LOD) of 4.26 mu g/kg, an over 200-fold improvement in the detection power was obtained based on the comparison of LODs of the developed method and FAAS. Applicability and accuracy of the developed method were validated by spike recovery results that fell in the range of 89-106 %, using the matrix matching method to boost quantification accuracy in the soil samples.
Keywords: Colloidal gel; deep eutectic solvent; dispersive solid phase extraction; nanoparticles; trace analysis; ATOMIC-ABSORPTION-SPECTROMETRY; LIQUID-LIQUID MICROEXTRACTION; PLATINUM-GROUP ELEMENTS; CLOUD POINT EXTRACTION; TRACE AMOUNTS; ROAD DUST; PALLADIUM; CATALYSTS; ELECTRODEPOSITION; RELEASE; Chemistry